Evaluation and mitigation analysis of carbon footprint for an airline operator: Case of Nepal airlines corporation - Tuladhar, Sandeep; Bajracharya, Tri Ratna; Shakya, Shree Raj (Journal of Innovations in Engineering Education, 2021)
This paper deals with evaluation and analysis of carbon footprint of an airline operator, Nepal Airlines Corporation (NAC) by using its actual flight and maintenance data from 2016 to 2019. NAC is a multi-fleet operator, of both turboprop and turbofan aircrafts. Carbon footprint in terms of Carbon Dioxide (CO2) emission has been calculated for NAC’s airline operations per individual aircraft, fleet-type and operating sector (i.e., international and domestic), and total ground handling operations. In each of the study years, contribution to NAC’s total CO2 production from its domestic fleet was found out to be very small (below 6% of yearly total), even though its fleet number outnumbered that of international fleet. This indicates better optimization opportunities for international-sector (turbofan) aircrafts than domestic-sector (turboprop) aircrafts. Reductions in fuel on-board as per prescribed levels, better airport slot management and selection of long-haul flight destinations have been identified as potential mitigation strategies for CO2 emission from international sector. Smaller aircrafts operating in domestic sectors are more prone to variations in occupancy rate and as such, NAC could focus on optimizing its commercial strategy to improve its CO2/passenger rate in domestic sector.